Modernizing Energy Efficiency Improvement With q-Rung Orthopair Fuzzy MULTIMOORA Approach - Muhammad Riaz; Hafiz Muhammad Athar Farid; Hafiz Muhammad Shakeel; Yahya Almalki (IEEE Access, 2022)
Low quality home energy appliances and cables are responsible for huge electricity wastage in low-income households. Absence of energy efficiency appliances standards and labeling and a policy for low-income households are among the main causes of electricity bleeding in developing countries. Energy efficiency standards and labeling for appliances and cables initiative can save significant amount of energy in Pakistan. In this paper, we used four alternatives for energy efficiency improvement for low income households at national level in Pakistan. For this we developed an extended “multi-criteria decision-making” (MCDM) approach to choose best alternative as a solution that should be able to evaluate and select the best scenario of energy efficiency with respect to eight criteria. We also developed the q-ROF Einstein aggregation operators based MULTIMOORA approach. This approach is a new hybrid technique that is more efficient to capture uncertain and incomplete assessments of stakeholders in terms of q-ROFNs. MCDM approaches are effective tools for solving energy decision-making challenges. Our results show that adoption of standards and labeling criteria for home appliances can improve living standards of low income households. This adoption has great potential to conserve electricity, environment and cost with introducing low income energy policy at government level.